Kinetic‐Pharmacodynamic Model of Platelet Time Course in Patients With Moderate‐to‐Severe Atopic Dermatitis Treated With Oral Janus Kinase 1 Inhibitor Abrocitinib. (22nd September 2020) - Soto, Elena; Banfield, Christopher; Gupta, Pankaj; Peterson, Mark C.
Abstract : The oral Janus kinase 1 (JAK1) inhibitor abrocitinib reduced signs and symptoms of atopic dermatitis (AD) in a placebo‐controlled, randomized, double‐blind, phase IIb trial (dose range 10–200 mg). A kinetic‐pharmacodynamic (K‐PD) model consisting of proliferation, maturation, and blood circulation compartments was developed to characterize platelet count changes during the study. The K‐PD model consisted of a drug elimination constant, four system parameters describing platelet dynamics, variance terms, correlation, and residual errors. Overall, these patients exhibited mean transit time from progenitor cells to platelets of 8.2 days (longer than the reported megakaryocyte life span), likely arising from JAK1‐induced perturbations of platelet progenitor homeostasis. The final model described dose‐related platelet count declines until nadir at treatment week 4 and return to baseline levels thereafter. The model was deemed suitable to support the design of subsequent abrocitinib AD trials and indicated limited clinically relevant platelet reductions in the range of doses studied.